Research on Marketing Planning of Tea Culture Ecotourism - Yang, Bo (International Journal of Global Economics and Management, 2024)
As the tempo of modern life accelerates, an increasing number of individuals are aspiring to a leisurely and natural way of living, leading to the burgeoning popularity of tea culture and ecotourism. This form of tourism allows travelers to immerse themselves in the tranquility of nature while savoring the profound heritage of tea culture. This novel fusion of traditional culture and ecotourism has invigorated the tourism market with fresh vitality. On a global scale, growing concerns for environmental conservation and cultural preservation have placed ecotourism under the spotlight. Tea, hailed as the "nectar of the nation," carries a rich tapestry of culture and history, luring travelers in search of deeper exploration. Against this backdrop, effective marketing strategies are paramount in enhancing the allure of tea culture ecotourism and promoting its sustainable development. Through meticulously planned promotional campaigns, enterprises involved in tea culture ecotourism can better attract their target audience, elevate brand recognition, and achieve a harmonious convergence of cultural and economic benefits.